Developing ˜Islam and Religious Moderation Course Based on Kampus Merdeka in Islamic Higher Education - Jamin, Ahmad; Mudra, Heri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The focus of the research is the development of the subject